Preparation method of molecular confinement fluorescent hydrogel and fluorescence regulation and control method of molecular confinement fluorescent hydrogel
By using controllable self-assembled polymer chains to form a dense structure in fluorescent gels, limiting molecular movement, achieving the generation of sequential fluorescence, and performing multi-mode regulation, it solves the complex preparation and fluorescence problems of fluorescent gels in the existing technology. The problem of difficult control is solved, and the effects of simplified preparation and real-time control are achieved.
Patent Information
- Application Number
- CN202411585092.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-07
- Publication Date
- 2025-01-14
AI Technical Summary
The existing fluorescent gel materials rely on complex organic chemical synthesis during the preparation process, making it difficult to achieve real-time fluorescence regulation, and the poor water-phase solubility of fluorescent dyes limits their application in hydrogel and biochemical systems.
The controllable self-assembly of polymer chains forms a dense structure to restrict molecular movement, thereby achieving the generation of sequential fluorescence, and using the controllability of polymer self-assembly to perform multi-mode and wide-range fluorescence regulation.
It simplifies the preparation process of fluorescent gels, enables the gel molecular network to generate fluorescence by itself without relying on traditional conjugated chromophores, and demonstrates great potential for functional applications.
Smart Images

Figure CN119306865A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to a method for preparing ordered fluorescent hydrogel and performing multi-mode fluorescence regulation by limiting molecular motion through controllable self-assembly. The present invention belongs to the field of polymer functional materials. Background Art
[0002] When certain substances are irradiated with incident light of a specific wavelength, they absorb light energy and enter an excited state, and then immediately de-excite and emit light with a longer wavelength than the incident light, which is called fluorescence. Fluorescence has excellent chemical selectivity, sensitivity, response rate, etc., and is widely used in optoelectronic devices, bioimaging, sensor detection and other fields. Hydrogel is an elastic material with a hydrophilic three-dimensional polymer network. It has many excellent properties in an aqueous environment, such as mechanical toughness, responsiveness to external stimuli, biocompatibility, self-healing, etc. Therefore, the fluorescent hydrogel prepared by combining fluorescent molecules and hydrogels can be used to develop promising flexible luminescent materials due to its comprehensive performance advantages.
[0003] The traditional preparation method of fluorescent gel mainly relies on chemical synthesis, that is, using organic chemical methods to design and synthesize molecules with fluorescent chromophores (generally containing highly conjugated structures), and then performing necessary chemical modifications on them so that they can be combined with the polymer network that constitutes the hydrogel, thereby being introduced into the gel material. Although the above methods have been widely used, there are still technical limitations. First, the traditional design and development model of fluorescent molecules requires a complex organic synthesis process, and it is difficult to modify and optimize fluorescent dyes. Secondly, the chemical structure of traditional fluorescent dyes is fixed, and it is difficult to regulate their luminescent properties in real time in actual application scenarios. Finally, the introduction of fluorescent dyes may affect some of the physical and chemical properties of the gel.
[0004] In recent years, the new idea of using fluorescent dyes with aggregation-induced emission (AIE) characteristics to prepare fluorescent gels has begun to attract widespread attention. AIE fluorescent dye molecules do not emit light or have very weak fluorescence in an isolated state. In an aggregated state, due to the molecular planarization and restricted molecular motion, their fluorescence is greatly enhanced. Molecules with AIE characteristics generally contain conjugated groups connected by rotatable σ bonds. A major advantage of AIE is that its fluorescence regulation does not depend on changes in molecular structure, but is based on changes in the molecular sequence state. Therefore, in situ and real-time efficient fluorescence regulation can be achieved, showing the unique advantages of sequence mode fluorescence over chemical structure fluorescence. However, the current AIE-based sequence fluorescence system still has certain limitations. First, the preparation of AIE fluorescent dyes still requires the use of a large number of chemical synthesis methods. Secondly, the aggregation and depolymerization of AIE fluorescent dyes usually rely on changes in the composition of external solvents, which has many restrictions on the use environment. Finally, since AIE molecules generally have multiple conjugated hydrophobic groups, their water solubility is naturally poor, which affects their application in hydrogels and biochemical systems. Therefore, it is urgent to develop innovative structure-controlled fluorescent systems, break through existing technical bottlenecks, and promote the further development and application of fluorescent gel materials. Summary of the invention
[0005] In response to the above technical needs and research bottlenecks, the inventors of this application have developed a design and preparation method for an original molecular confined fluorescent hydrogel, and named this type of material system as confinement-induced fluorescence (CIE) gel. The intermolecular forces drive the controllable self-assembly of the gel polymer chain to produce a dense high-level structure, which effectively restricts its own movement, so that the gel molecular network itself can also produce structured fluorescence in the absence of traditional conjugated chromophores, greatly simplifying the fluorescent gel preparation process. At the same time, based on the high controllability of polymer self-assembly, the fluorescence of the CIE system is regulated in situ in a multi-mode and large range, showing great functional application potential.
[0006] The working principle of the CIE system is: the aggregation state of polyacrylic acid type polymer and 1,2-diamine type molecular unit undergoes a controllable transformation driven by their characteristic intermolecular interaction, and the polymer chain can complete the transformation from a stretched form to an ordered aggregation form. This transformation can greatly restrict the movement of molecules in a highly aggregated state, thereby generating enhanced fluorescence emission ( Figure 1 ).
[0007] The preparation method of the fluorescent hydrogel proposed by the present invention comprises the following steps:
[0008] (1) Prepare hydrogen bond donor stock solution: Dissolve the hydrogen bond donor in deionized water to form a stock solution.
[0009] The concentration should be adjusted according to the required performance of the material. Usually the mass concentration of the stock solution is 25%-50%. The hydrogen bond donor that can be used to prepare fluorescent hydrogels is acrylic acid (AAc) or acrylic acid derivatives with α-substituents, such as methacrylic acid (MAAc), 2-fluoroacrylic acid (FAAc), etc.
[0010] (2) Mix the reactants in a certain proportion: mix the hydrogen bond donor stock solution with the hydrogen bond acceptor, deionized water, and ammonium persulfate solution (APS). The mass concentration of the ammonium persulfate solution is generally 5%-10%, and the volume fraction is 1%-10%. The molar ratio of the hydrogen bond donor to the acceptor in the final mixed solution ranges from 25:1 to 4:1, and the mass concentration of the hydrogen bond donor ranges from 20% to 38%. The hydrogen bond acceptors that can be used to prepare CIE fluorescent hydrogels include ethylenediamine (EDA), diethylenetriamine (DETA), triethylenetetramine (TETA), pentaethylenehexamine (PEHA), 1,1,4,7,10,10-hexamethyltriethylenetetramine (HMTETA), tetramethylethylenediamine (TEMED), N,N,N',N'-tetraethylethylenediamine (TEEED), trans-1,4-cyclohexanediamine (trans-CHDA), cis-1,4-cyclohexanediamine (cis-CHDA), etc.
[0011] (3) A certain amount of chemical crosslinking agent can be added to the reactants mixed in the above steps to improve the mechanical strength and stability of the final product. The addition of the crosslinking agent does not affect the fluorescence characteristics of the product. The chemical crosslinking agent that can be used to prepare CIE fluorescent hydrogel can be N, N'-methylenebisacrylamide (Bis), polyethylene glycol diacrylate, pentaerythritol tetraacrylate, pentaerythritol triacrylate, etc. The amount of the crosslinking agent is usually 0.5-10 mg / mL of the mixed solution.
[0012] (4) Standing: Place the reaction mixture in a sealed container and wait for it to solidify. Depending on the formulation, the solidification time will vary greatly, generally between 5 minutes and 1 day. After solidification, CIE hydrogel is formed. If a fluorescent hydrogel of a specific shape needs to be prepared, the reaction mixture can be poured into the corresponding mold, and the desired sample will be formed after solidification.
[0013] Since CIE is a sequence-configuration fluorescence, the self-assembly of the gel molecular network can be regulated by changing the system components and the external environment, thereby achieving multi-mode, large-scale continuous regulation of CIE fluorescence. The fluorescence hydrogel prepared in the present invention can be regulated by the following method:
[0014] (1) Prepare CIE fluorescent hydrogel according to the above steps, place the gel on a heating table, change the temperature of the heating table (usually in the range of 10°C-100°C), the fluorescence intensity of the gel will decrease as the temperature increases, and when the temperature drops, the fluorescence intensity will gradually recover. Gels prepared with different formulas respond differently to temperature.
[0015] (2) Prepare CIE fluorescent hydrogel according to the above steps and place it in a pH buffer. The fluorescence intensity of the gel responds differently to the immersion time and the type of pH buffer. The buffer system that can be used to regulate CIE fluorescence is phosphoric acid-sodium dihydrogen phosphate, acetic acid-sodium acetate, disodium hydrogen phosphate-sodium dihydrogen phosphate, etc. The pH range of the buffer is usually 2.00-8.00, and the ionic strength is 0.1000-1.0000.
[0016] (3) Prepare a CIE fluorescent hydrogel plate using a mold according to the above steps. Use a stamp with a raised pattern to press the gel plate, and an obvious fluorescence enhancement phenomenon can be observed at the place where the gel is pressed and deformed by a fluorescence microscope. The reduction rate of the gel thickness at the pressing point should generally be 20%-90%, and the pressing time should be 5 seconds-30 seconds. BRIEF DESCRIPTION OF THE DRAWINGS
[0017] Figure 1 Schematic diagram of the CIE fluorescent hydrogel principle.
[0018] Figure 2 Microscopic photos of CIE fluorescent hydrogel in Example 1. (A) Transmission microscopic photo of CIE fluorescent gel; (B) Fluorescence microscopic photo of CIE fluorescent gel.
[0019] Figure 3 Continuous regulation of fluorescence based on changes in gel composition in Example 2. (A) Transmission micrograph and fluorescence micrograph of CIE fluorescent gel; (B) Change trend of gel fluorescence intensity and transmittance intensity with amine concentration; (C) Micrographs of gels with PEHA contents of 80, 120, 160, and 200 μL, respectively.
[0020] Figure 4 Fluorescence photograph of CIE gel fluorescence regulated by temperature in Example 3.
[0021] Figure 5 Relative fluorescence intensity of the CIE fluorescent gel heating and cooling cycle in Example 4.
[0022] Figure 6 In Example 5, the fluorescence of the CIE gel is affected by pH.
[0023] Figure 7 The fluorescence of CIE gel is regulated by strain in Example 6. (A) Stamp pattern; (B) Fluorescence photo of PEHA gel after stamp pressing.
[0024] Figure 8 Fluorescent self-healing properties of CIE gel in Example 7. Wherein t0 = 0 min, t1 = 20 min, t2 = 29 min, t3 = 37 min, t4 = 42 min, t5 = 1 day.
[0025] Fig. 9 The gelation and fluorescence emission of the system containing 1,6-hexanediamine in Comparative Example 1.
[0026] Fig.10 The gelation and fluorescence emission of the trimethylamine system in Comparative Example 2.
[0027] Fig.11 Comparative Example 3 contains hexamethylenetetramine for colloid formation and fluorescence emission.
[0028] Fig.12 Comparison of fluorescence intensity of amine solution, precursor and gel in Comparative Example 4. DETAILED DESCRIPTION
[0029] The present invention will be further described below in conjunction with examples, but the present invention is not limited to the following examples.
[0030] Embodiment 1:
[0031] Prepare a 44.4% AAc stock solution. Add 100 μL DETA, 100 μL H2O and 100 μL 10 wt.% APS to 1 mL AAc stock solution, mix well and inject into a mold with a cavity thickness of 1 mm. Leave it for one day to obtain CIE fluorescent hydrogel. Take the CIE gel out of the mold. The formed gel is opaque under a microscope ( Figure 2 A), obvious fluorescence phenomenon can be observed through fluorescence microscopy ( Figure 2 B).
[0032] Embodiment 2:
[0033] Prepare an AAc stock solution with a mass fraction of 44.4%. Take 7 test tubes and add 1 mL of AAc stock solution to each. Add 20, 30, 40, 80, 120, 160, and 200 μL of PEHA and corresponding volumes of deionized water to different test tubes, respectively, so that the total volume of the two is 200 μL. Add 100 μL of 10 wt.% APS to all test tubes, mix each test tube evenly, and inject them into a mold with a cavity thickness of 1 mm. Place them for 8 hours to obtain a series of CIE fluorescent hydrogels. The CIE gel was taken out of the mold, and under a microscope, it can be observed that the transmittance and fluorescence of the gel changed significantly with the change of PEHA content ( Figure 3A), the fluorescence intensity and light transmittance of each gel were measured by a multifunctional spectrometer. The fluorescence intensity first increased and then decreased with the change of amine concentration. The light transmittance of the gel showed the opposite trend ( Figure 3 B). Through a microscope, it can be observed that there are granular structures in the gel, which are dense phases formed by the aggregation of gel polymer chains. The density change trend is consistent with the light intensity change curve ( Figure 3 C). This shows that there is a clear correlation between the polymer structure of the gel and the fluorescence enhancement.
[0034] Embodiment 3:
[0035] Prepare an AAc stock solution with a mass fraction of 44.4%. Take 5 test tubes and add 1 mL of AAc stock solution to each. Add 35, 40, 43, 45, and 50 μL of PEHA to different test tubes and add the corresponding volume of deionized water so that the total volume of the two is 200 μL. Add 100 μL of 10wt.% APS to all test tubes, mix well, and inject them into molds with a cavity thickness of 1 mm. Let stand for 4 hours to obtain CIE fluorescent gel. Adjust the temperature of the heating table to the target temperature, place the CIE gel on the heating table, balance for 60 seconds, and take fluorescent photos using a fluorescence microscope. According to the above operation, take fluorescent photos of CIE gels with PEHA contents of 35, 40, 43, 45, and 50 μL at 20, 25, 30, 35, 40, 50, 60, and 70°C in turn ( Figure 4 ). The results confirmed that the fluorescence of CIE gel can be regulated by changing the temperature.
[0036] Embodiment 4:
[0037] Prepare an AAc stock solution with a mass fraction of 44.4%. Add 40μL PEHA, 160μL H2O and 100μL 10wt.% APS to 1mL AAc stock solution. After mixing evenly, inject into a mold with a cavity thickness of 1mm and let it stand for one day to obtain CIE fluorescent gel. The temperature of the heating table is set to room temperature (25℃), and the CIE gel is placed on the heating table. It is kept warm for 60 seconds to stabilize the fluorescence of the gel, and the fluorescence intensity is measured by a multi-functional spectrometer. Remove the CIE fluorescent gel, heat the heating table to 40℃, place the CIE fluorescent gel after the temperature stabilizes, and keep it warm for 60 seconds to stabilize the fluorescence of the gel. The fluorescence intensity at this time is measured by a multi-functional spectrometer. Remove the CIE fluorescent gel, cool the heating table to 25℃, repeat the above operation, and repeat this process. Each room temperature-heating measurement is a cycle, and the fluorescence data of 7 cycles are measured according to the above steps ( Figure 5 ). This shows that CIE gel has good fluorescence temperature-sensitive reversibility and stability.
[0038] Embodiment 5:
[0039] Prepare an AAc stock solution with a mass fraction of 44.4%. Take 3 test tubes and add 1 mL of the stock solution and 2 mg of Bis to each. Add 35, 40, and 60 μL of PEHA to different test tubes, respectively, and add the corresponding volume of deionized water so that the total volume of the two is 200 μL. Add 100 μL of 10 wt.% APS to all test tubes, mix well, and inject into a flat mold of the same size with a cavity thickness of 1 mm. Let it stand for one day to obtain CIE gel. The CIE gel was soaked in a phosphate-sodium dihydrogen phosphate buffer with an ionic strength of 1.0000 and a pH of 2.12. The fluorescence intensity of the prepared state and the swollen state (immersed for 1 hour) was recorded by a multifunctional spectrometer. The fluorescence of gels with different amine contents has different responses to the same buffer ( Figure 6 ). This shows that the fluorescence of CIE gel can be regulated by external pH.
[0040] Embodiment 6:
[0041] Prepare a 44.4% AAc stock solution. Add 0.5 mg Bis, 32 μL PEHA, 168 μL H2O and 100 μL 10 wt.% APS to 1 mL AAc stock solution. After mixing well, inject the reactant solution into a 1 mm thick flat mold and let it stand for one day to obtain a CIE gel. Take the gel out of the mold and stamp it with a stamp with a specific shape ( Figure 7 A) Press for 10 seconds until the deformation rate at the pressed position reaches 75%. Fluorescence enhancement was observed at the gel deformation position using a fluorescence microscope ( Figure 7 B). Demonstrates that the fluorescence of CIE gels can be regulated by strain.
[0042] Embodiment 7:
[0043] Prepare an AAc stock solution with a mass fraction of 44.4%. Add 35μL PEHA, 165μL H2O and 100μL 10wt.% APS to 1mL AAc stock solution, mix well, and then inject the reactant solution into a 2mm thick flat mold and let it stand for one day to obtain a CIE gel. Take the gel out of the mold, pierce the gel with a needle tip, and place it under a fluorescence microscope for continuous photography. There is no fluorescence at the location where the gel has just been destroyed (t0). As time goes by, the destroyed area gradually shrinks. After a period of time, the gel completely recovers to its original state (t5) and the fluorescence almost returns to its original state (t7). Figure 8 ). This shows that the fluorescence self-healing properties of CIE gels make the fluorescence emission of this type of material highly robust.
[0044] Comparative Example 1:
[0045] Prepare an AAc stock solution with a mass fraction of 44.4%. Take 6 test tubes and add 1 mL of the stock solution to each. Add 20, 40, 80, 120, 160, and 200 μL of 1,6-hexanediamine to different test tubes and add the corresponding volume of deionized water so that the total volume of the two is 200 μL. Add 100 μL of 10 wt.% APS to all test tubes, mix well, and let it stand for one day without gelling. Inject the solution that has been reacted for one day into a hollow mold with a cavity thickness of 1 mm, and measure the fluorescence intensity using a multi-function spectrometer. The fluorescence intensity of the 6 groups of solutions is close to 0 ( Fig. 9 ). This indicates that 1,6-diamine (non-1,2-diamine type molecule) cannot produce CIE fluorescence.
[0046] Comparative Example 2:
[0047] Prepare an AAc stock solution with a mass fraction of 44.4%. Take 6 test tubes and add 1 mL of the stock solution to each. Add 20, 40, 80, 120, 160, and 200 μL of trimethylamine to different test tubes, respectively, and add the corresponding volume of deionized water so that the total volume of the two is 200 μL. Add 100 μL of 10 wt.% APS to all test tubes, mix well, and let it stand for one day without gelling. Inject the solution that has been reacted for one day into a hollow mold with glass on the top and bottom and a thickness of 1 mm in the middle, and measure the fluorescence intensity with a multi-function spectrometer. The fluorescence intensity of the 6 groups of solutions is close to 0 ( Fig.10 ). This indicates that monoamines (non-1,2-diamine molecules) cannot produce CIE fluorescence.
[0048] Comparative Example 3:
[0049] Prepare AAc stock solution with a mass fraction of 44.4%. Take 4 test tubes and add 1 mL of stock solution to each. Add 20, 40, 60, and 100 mg of hexamethylenetetramine to different test tubes and add 180, 160, 140, and 100 μL of deionized water, respectively. Add 100 μL of 10 wt.% APS to all test tubes, mix well, and let stand for one day without gelling. Inject the solution that has been reacted for one day into a hollow mold with glass top and bottom and a thickness of 1 mm in the middle, and measure the fluorescence intensity with a multi-function spectrometer. The fluorescence intensity of the four groups of solutions is close to 0 ( Fig.11 ). This indicates that 1,1-diamine (not 1,2-diamine type molecules) cannot produce CIE fluorescence.
[0050] Comparative Example 4:
[0051] Take 1.2 mL of deionized water in a test tube, add 100 μL of PEHA, mix well, inject the solution into a hollow mold with a cavity thickness of 1 mm, and measure the fluorescence intensity using a multifunctional spectrometer.
[0052] Prepare AAc stock solution with a mass fraction of 44.4%. Take 1 mL of AAc stock solution in a test tube, add 100 μL of PEHA and 200 μL of deionized water. Mix well, inject the solution into a hollow mold with a cavity thickness of 1 mm, and measure the fluorescence intensity using a multifunctional spectrometer.
[0053] Prepare AAc stock solution with a mass fraction of 44.4%. Take 1mL of AAc stock solution in a test tube, add 100μL PEHA, 100μL deionized water and 100μL 10wt.% APS. Mix well, inject the solution into a hollow mold with a cavity thickness of 1mm, let it stand for 40 minutes to form a gel, and measure the fluorescence intensity by a multifunctional spectrometer. The comparison of the above three sets of data shows that ( Fig.12 ), before gelation, the amine solution and the precursor had no obvious fluorescence intensity. After gelation, the fluorescence intensity was greatly improved, which shows that the fluorescence of CIE gel is caused by the special sequence structure of gel polymer, not the original characteristics of the reactants themselves.
Claims
1. A method for preparing a molecular confined fluorescent hydrogel, characterized in that: The following steps are involved: (1) preparing a hydrogen bond donor stock solution: dissolving the hydrogen bond donor in deionized water to form a stock solution, wherein the mass concentration of the stock solution is 25%-50%; the hydrogen bond donor used to prepare the fluorescent hydrogel is acrylic acid or an acrylic acid derivative having an α-substituent; (2) Mixing reactants: mixing a hydrogen bond donor stock solution with a hydrogen bond acceptor, deionized water, and an ammonium persulfate solution to obtain a reaction mixture; the mass concentration of the ammonium persulfate solution is 5%-10%, and the volume fraction of the ammonium persulfate solution in the reaction mixture is 1%-10%; the molar ratio of the hydrogen bond donor to the acceptor in the reaction mixture is in the range of 25:1-4:1, and the mass concentration of the hydrogen bond donor is in the range of 20%-38%; the hydrogen bond acceptor is ethylenediamine (EDA), diethylenetriamine (DETA), triethylenetetramine (TETA), pentaethylenehexamine (PEHA), 1,1,4,7,10,10-hexamethyltriethylenetetramine (HMTETA), tetramethylethylenediamine (TEMED), N,N,N',N'-tetraethylethylenediamine (TEEED), trans-1,4-cyclohexanediamine (trans-CHDA) or cis-1,4-cyclohexanediamine (cis-CHDA); (3) Standing: The reaction mixture is placed in a sealed container and allowed to solidify for a period of 5 minutes to 1 day. After solidification, a CIE hydrogel is formed.
2. The method according to claim 1, characterized in that: A chemical crosslinking agent is added to the reaction mixture, wherein the chemical crosslinking agent is N,N'-methylenebisacrylamide, polyethylene glycol diacrylate, pentaerythritol tetraacrylate or pentaerythritol triacrylate, and the amount of the crosslinking agent is 0.5-10 mg / mL of the reaction mixture.
3. The method according to claim 1, characterized in that The prepared hydrogel is subjected to fluorescence regulation according to one of the following methods: (1) Prepare CIE hydrogel, place the gel on a heating table, and change the temperature of the heating table. The temperature range is usually 10°C-100°C. The fluorescence intensity of the gel will decrease as the temperature increases. When the temperature decreases, the fluorescence intensity will gradually recover. (2) CIE hydrogel was prepared and placed in a pH buffer; the fluorescence intensity of the gel had different responses with the immersion time and the type of pH buffer; the buffer system used to regulate CIE fluorescence was phosphate-sodium dihydrogen phosphate, acetic acid-sodium acetate or disodium hydrogen phosphate-sodium dihydrogen phosphate, the pH range of the buffer was 2.00-8.00, and the ionic strength was 0.1000-1.0000; (3) A CIE hydrogel plate is prepared using a mold; a stamp with a raised pattern is used to press the gel plate, and fluorescence enhancement is observed at the gel pressing deformation site using a fluorescence microscope; the gel thickness reduction rate at the pressing site is 20%-90%, and the pressing time is 5 seconds-30 seconds.
Citation Information
Cited By
Fluorescent color-changing hydrogel material based on crystallization / melting reversible phase change regulation and control as well as preparation method and application of fluorescent color-changing hydrogel material
CN121652337A